Students’ Perceptions Of Budget Transparency In Public Sector Financial Management - Evi Rosdiyanti; Noni Antika Kharunnisah (Business Management, 2026)
This study aims to analyze students' perceptions of budget transparency in public sector financial management. Budget transparency is an essential element of good governance that supports accountability, public oversight, and trust in public institutions. This study used a quantitative approach with a survey method. Respondents consisted of 50 second-semester students of the Public Sector Financial Management Study Program at the Lombok Business Academy. Data were collected through a structured questionnaire using a five-point Likert scale that measured several indicators of budget transparency, including accountability, public access to information, and the role of transparency in preventing budget misuse. Data were analyzed using descriptive statistical analysis by calculating the mean value to determine students' perceptions. The results showed that students generally had a positive perception of budget transparency. Students believed that transparency plays a crucial role in enhancing institutional accountability, facilitating public oversight, and reducing the potential for misuse of public funds. These findings imply that integrating the concepts of transparency and accountability into public sector financial management education is crucial for developing students' competencies as future public finance practitioners who are professional, transparent, and accountable.